The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1128/aem.01533-18
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacterial Microbiota of Coastal Halophyte Limonium sinense and Amelioration of Salinity Stress Damage by Symbiotic Plant Growth-Promoting Actinobacterium Glutamicibacter halophytocola KLBMP 5180

Abstract: Plant-associated microorganisms are considered a key determinant of plant health and growth. However, little information is available regarding the composition and ecological function of the roots' and leaves' bacterial microbiota of halophytes. Here, using both culture-dependent and culture-independent techniques, we characterized the bacterial communities of the roots and leaves as well as the rhizosphere and bulk soils of the coastal halophyte in Jiangsu Province, China. We identified 49 representative bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 100 publications
2
52
0
Order By: Relevance
“…increased growth and development of maize under drought and salinity through accumulation of proline and soluble sugars (Vardharajula et al, 2011). Role of the trehalose as an osmoprotectant under salt-stress is also well documented and a large number of ST-PGPR have been discovered having genes for trehalose biosynthetic pathways (Qin et al, 2018;Orozco-Mosqueda et al, 2019;Shim et al, 2019).…”
Section: Osmoprotectantsmentioning
confidence: 99%
“…increased growth and development of maize under drought and salinity through accumulation of proline and soluble sugars (Vardharajula et al, 2011). Role of the trehalose as an osmoprotectant under salt-stress is also well documented and a large number of ST-PGPR have been discovered having genes for trehalose biosynthetic pathways (Qin et al, 2018;Orozco-Mosqueda et al, 2019;Shim et al, 2019).…”
Section: Osmoprotectantsmentioning
confidence: 99%
“…The main drivers for the reduction or abundance of these phyla were Micromonospora , Kibdelosporangium , and Iamia (Actinobacteria), Terriglobus (Acidobacteria), Isosphaera (Planctomycetes), and Chthoniobacter (Verrucomicrobia; Table 4 ). In our study, an increase in relative abundance of dominant Actinobacteria (Gram-positive bacteria) was primarily associated with the presence of halo-tolerant bacteria, such as Micromonspora ( Ballav et al, 2015 ), Iamia ( Plotnikova et al, 2011 ; Ma and Gong, 2013 ), and Kibdelosporangium ( Qin et al, 2018 ). Abdulla (2009) found that Kibdelosporangium and Nocardioides were potential members of Actinomycetes, which played multiple roles in rock weathering, such as metal leaching, acid production, and the solubilization of phosphate and sulfate.…”
Section: Discussionmentioning
confidence: 59%
“…Iamia (Plotnikova et al, 2011;Ma and Gong, 2013), and Kibdelosporangium (Qin et al, 2018). Abdulla (2009) found that Kibdelosporangium and Nocardioides were potential members of Actinomycetes, which played multiple roles in rock weathering, such as metal leaching, acid production, and the solubilization of phosphate and sulfate.…”
Section: Water Addition Alters Soil Microbial Community Structures Thmentioning
confidence: 99%
“…Many ST-PGPRs showed a high expression of genes implicated in trehalose biosynthetic pathways (e.g. trehalose 6-phosphate gene) ( Qin et al., 2018 ). Trehalose is an osmoprotectant, and its role in salt-stress tolerance has been well documented ( Garg et al., 2019 ; Orozco-Mosqueda et al., 2019 ; Shim et al., 2019 ).…”
Section: Strategies For Increasing Salt Stress Tolerancementioning
confidence: 99%